Antioxidant, Cytotoxicity and Polyphenolic Content of Calotropis procera (Ait.) R. Br. Flowers - M. Rama Prabha, K. Vasantha (Journal of Applied Pharmaceutical Science)
AbstractOxidative stress has been implicated with the pathology of many diseases such as inflammatory conditions, cancer, diabetes and aging. In view of that an attempt was made to evaluate free radical scavenging activity, cytotoxic activity and polyphenolic content of methanolic extract of Calotropis procera flowers.Free radical scavenging activity was estimated using in vitro models like 1,1,-diphenyl-2- picryl hydrazyl (DPPH), hydroxyl radical, hydrogen peroxide radical, reducing power and ferric thiocyanate method. Cytotoxicity was analysed following MTT assay using Hep2 and Vero cell lines and polyphenols were estimated using standard methods. Two way ANOVA was used for statistical analyses. The methanol extract of C. procera at 500 µg/ml showed better scavenging activity in ferric thiocyanade method (83.63 %) with the lowest IC50 of 100 µg/ml followed by hydrogen peroxide, hydroxyl radical scavenging and least activity was found to be present in DPPH assay (50.82 %). The extract had 100 % cytotoxicity on Hep2 cell lines. Flavonoids were found in greater amount than phenols and found to be had higher correlation with antioxidant activities. It was suggested that the flowers of C. procera possess in vitro antioxidant, cytotoxic activities and thus having much therapeutic value because of their polyphenolic content.
Keywords: Antioxidant, Calotropis procera, cytotoxicity, polyphenol.